Factors leading to customer satisfaction: an empirical study of retail banking in Oman. (2018) - Ananda, S.; Devesh, Sonal
The banks have been focusing on customer oriented services for their sustainability and growth due to competitive environment. As banks deal with homogeneous products and services, the quality of their service play a vital role in achieving customer satisfaction. The main purpose of this paper is to explore the factors influencing the service quality of banks leading to customer satisfaction. The primary data was collected through a structured questionnaire from 152 respondents from different banks in Oman. The study used factor analysis to identify the most influencing service quality dimensions in achieving customer satisfaction. The study found that reliability, responsiveness and assurance are the most influencing service quality dimensions that lead to customer satisfaction. The study helps the Omani banks to understand customers' perception of service quality and contributes ideas to develop strategies for customer retention and acquisition.